Entrepreneurship During the Era of Covid-19 (Evidence from Poland) - Magdalena WOJARSKA (Communications of International Proceedings, 2021)
The paper aimed to determine whether all enterprises in the 11 months covered by the analysis were equally negatively affected by the Covid-19 pandemic. Secondary data collected by Statistics Poland, as a part of the monthly survey of the economic situation, was used to achieve it. The analysis shows that not all entrepreneurs have felt the effects of the pandemic in the same way. Large entities, especially from the construction sector, are doing much better in this period. Micro-enterprises, especially in the hotel, and catering industry, (which due to restrictions, have had to suspend or significantly reduce their activities), are in a much worse situation. It is all the more worrying that the SME sector constitutes a significant part of enterprises in Poland (99.8%), and among them, the most numerous group (96.7%) are micro-enterprises. In 2017, small and medium-sized enterprises generated almost every second PLN of GDP (49.1%), with micro-enterprises having the largest share in GDP (approx. 30.3%). It means that the troubles of these enterprises will have a profound effect on the condition of the Polish economy soon.
Keywords: Entrepreneurship; Covid-19; Poland